Study of Manning’s value and Constants in Some Tertiary Channels Condition at Namu Sira Sira Irrigation Networks Namu Ukur Utara Village Sei Bingai Subdistrict Langkat District - Hisyam Pahlevi; Sumono Sumono; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Most of the tertiary irrigation in Namu Ukur Utara Village are land channels. This condition will affect the discharge and the water distribution efficiency for paddy field. The water distribution efficiency will be affected by water flow rate and channels condition, where both of this factor could be manifested through  the Manning’s value and Chezy constant. This research was aimed to determine  the Maning’s value and Chezy constant in 3 tertiary vegetated channels and trimmed channels at Namu Ukur Utara Village Namu Sira Sira Irrigation networks Langkat District. The Manning’s value coefficients for the three vegetated channels were 0,278; 0,268 and 0,185 and the Chezy constantwere 2,31; 2,48 and 3,63 respectively. While the Manning’s value coefficients for the trimmed channels were 0,247; 0,229 and 0,138 and the Chezy constant were 2,61; 2,90 and 4,66 respectively. Keyword : Chezy constant, Manning’s value coefficient, Tertiary Channels, Vegetation